Dinamika Hukum dalam Proses Perizinan Pembangunan Saluran Udara Tegangan Ekstra Tinggi di Sumatera Selatan - Rahmiko, Eko; Saputro, Adi; Sami’an, S. (SIGn Jurnal Hukum, 2024)
In order to meet the ever-increasing electricity demand in Indonesia, the development of EHV Overhead Lines has become crucial. This research examines the legal dynamics in the permitting process for EHV Overhead Line development in South Sumatra, which is identified as a major inhibiting factor for developing this infrastructure. This research uses a juridical-empirical approach with a case study in South Sumatra. Primary data were obtained through interviews with relevant stakeholders, while secondary data were collected by studying documents and regulations related to EHV Overhead Line permitting. The results show that regulatory complexity and community resistance shape the legal dynamics that hinder the permitting process. Regulatory complexity manifests in regulatory disharmony, overlapping authority among agencies, and complicated procedures. Community resistance arises due to land acquisition problems, infrastructure damage, concerns about health impacts, and a lack of transparency. These legal dynamics slow EHV Overhead Line development and hinder the optimization of energy resource potential in South Sumatra. Therefore, regulatory reform and improving permitting governance that focuses on simplification, harmonization, transparency, and public participation are urgently needed to support sustainable power infrastructure development.